Electrode stack and method for manufacturing the same
Patent Information
- Application Number
- JP2025062669
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-04
- Publication Date
- 2026-10-16
AI Technical Summary
【0012】 本開示の電極積層体及びその製造方法によれば、集電体層とその上に積層される活物質層との密着性を改善できる。
Smart Images

Figure 2026169031000001_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present disclosure relates to an electrode laminate and a method for manufacturing the same.
BACKGROUND ART
[0002] In current collector layers for batteries such as lithium ion batteries, particularly in current collector layers for laminated lithium ion secondary batteries, delamination may occur between the current collector layer and the active material layer laminated thereon, and when such delamination occurs, battery performance is degraded.
[0003] Accordingly, studies have been conducted to form recesses in the current collector layer or the carbon coat layer formed on the current collector layer to improve the adhesion between the current collector layer and the active material layer laminated thereon, thereby suppressing delamination therebetween.
[0004] In this regard, for example, Patent Document 1 discloses that by forming recesses on the surface of the current collector layer, the interface area between the current collector layer and the layer in contact therewith can be increased to reduce the contact electrical resistance, and the adhesion and adhesiveness between the current collector layer and the layer in contact therewith can be enhanced to firmly bond the current collector layer and the layer in contact therewith.
[0005] Further, Patent Document 2 discloses a carbon coat layer containing a carbon material provided on a current collector layer, which has a predetermined uneven pattern on the surface on the side in contact with active material particles, and the unevenness formed by the carbon material is provided on the surface having the uneven pattern. Further, Patent Document 2 states that the recesses constituting the uneven pattern may have a size larger than the maximum particle diameter of the active material particles.
PRIOR ART DOCUMENTS
PATENT DOCUMENTS
[0006]
PATENT DOCUMENT 1
PATENT DOCUMENT 2
[0007] As described in Patent Documents 1 and 2, it has been investigated to create recesses in the current collector layer or the carbon coating layer formed on the current collector layer, thereby improving the adhesion between the current collector layer and the active material layer laminated on top of it, and thereby suppressing delamination between them.
[0008] However, there is room for improvement regarding the adhesion between the current collector layer and the active material layer laminated on top of it.
[0009] This disclosure provides an electrode laminate that can improve the adhesion between a current collector layer and an active material layer laminated thereon, and a method for manufacturing the same. [Means for solving the problem]
[0010] After careful consideration, the Disclosing Parties have found that the above-mentioned problems can be solved by the following means, and have completed this disclosure. Specifically, this disclosure is as follows:
[0011] <Aspect 1> Current collector layer, and Active material layer placed on the above current collector layer An electrode laminate having, The current collector layer has a recess on the surface on which the active material layer is laminated, Some of the active material particles contained in the above active material layer are embedded in the above recesses. The width of the entrance to the recess is wider than the width of the central part of the recess. The inclination angle of the entrance portion of the recess with respect to the surface of the current collector layer is smaller than the inclination angle of the central portion of the recess with respect to the surface of the current collector layer. The width of the entrance to the recess is greater than the D50 particle diameter of the active material particles contained in the active material layer. The depth of the recess is greater than the D50 particle diameter of the active material particles contained in the active material layer. Electrode stack. <Aspect 2> The width of the entrance portion of the recess is 1.1 times or more the width of the central portion of the recess. The inclination angle of the entrance portion of the recess with respect to the surface of the current collector layer is 0.8 times or less the inclination angle of the central portion of the recess with respect to the surface of the current collector layer. The width of the entrance to the recess is 2.0 to 10.0 times the D50 particle diameter of the active material particles contained in the active material layer. The depth of the above recess is 2.0 to 10.0 times the D50 particle diameter of the active material particles contained in the above active material layer, and The depth of the recess is no more than 10.0 times the width of the entrance to the recess. The electrode laminate according to embodiment 1. <Aspect 3> A battery having an electrode stack according to embodiment 1 or 2. <Aspect 4> A method for manufacturing a current collector layer, Laminating a mask layer having openings onto the surface of a metal foil, The metal foil is etched through the openings in the mask layer to form preliminary recesses on the surface of the metal foil. Removing the above mask layer from the above metal foil, and The metal foil from which the mask layer has been removed is etched to obtain the current collector layer. including and The current collector layer has a recess on the surface on which the active material layer is laminated, The width of the entrance to the recess is wider than the width of the central part of the recess. The inclination angle of the entrance portion of the recess with respect to the surface of the current collector layer is smaller than the inclination angle of the central portion of the recess with respect to the surface of the current collector layer. A method for manufacturing a current collector layer. <Aspect 5> To manufacture a current collector layer by the method described in Embodiment 4, The active material layer slurry containing the above-mentioned active material particles is applied to the above-mentioned current collector layer. drying the above active material layer slurry to form the above active material layer, The method for producing an electrode laminate according to aspect 1 or 2, comprising: [Effects of the Invention]
[0012] According to the electrode laminate and the production method thereof of the present disclosure, the adhesion between the current collector layer and the active material layer laminated thereon can be improved. [Brief Description of the Drawings]
[0013] [Figure 1] Figure 1 is a schematic diagram of the electrode laminate of the present disclosure. [Figure 2] Figure 2 is a schematic diagram for explaining the current collector layer used in the electrode laminate of the present disclosure. [Figure 3] Figure 3 is a schematic diagram of a current collector layer used in a conventional electrode laminate. [Figure 4] Figure 4 is a schematic diagram for explaining the production process of the current collector layer used in the electrode laminate of the present disclosure. [Modes for Carrying Out the Invention]
[0014] <<Electrode Laminate>> As illustrated in Figures 1 and 2, the electrode laminate 100 of the present disclosure comprises a current collector layer 10 and an active material layer 20 disposed on the current collector layer 10. Here, the current collector layer 10 has a recess 10a on the surface on which the active material layer 20 is laminated, and a portion of the active material particles 25 contained in the active material layer 20 enters the recess 10a. Furthermore, the width of the entrance portion of the recess 10a is wider than the width of the central portion of the recess 10a, and the inclination angle α of the entrance portion of the recess 10a with respect to the surface of the current collector layer 10 is smaller than the inclination angle β of the central portion of the recess 10a with respect to the surface of the current collector layer 10. In addition, the width of the entrance portion of the recess 10a is greater than the D50 particle diameter of the active material particles 25 contained in the active material layer 20, and the depth of the recess 10a is greater than the D50 particle diameter of the active material particles 25 contained in the active material layer 20. Figures 1 and 2 are not intended to limit this disclosure in any way, but are merely illustrative examples of this disclosure.
[0015] According to the electrode laminate 100 of this disclosure as described above, the active material particles 25 contained in the active material layer 20 can easily penetrate into the recesses 10a of the current collector layer 10, and therefore the adhesion between the current collector layer 10 and the active material layer 20 laminated thereon can be improved.
[0016] In contrast, as shown in Figure 3(a), if the width of the entrance to the recess is smaller than the D50 particle diameter of the active material particles 25 contained in the active material layer 22, and / or if the depth of the recess is smaller than the D50 particle diameter of the active material particles 25 contained in the active material layer 22, the active material particles 25 contained in the active material layer 22 will have difficulty entering the recess of the current collector layer 10, and therefore it will be difficult to improve the adhesion between the current collector layer 10 and the active material layer 22 laminated on top of it.
[0017] Furthermore, as shown in Figure 3(b), if the width of the entrance to the recess is narrower than the width of the central part of the recess, and / or if the inclination angle α of the entrance to the recess with respect to the surface of the current collector layer 10 is greater than the inclination angle β of the central part of the recess with respect to the surface of the current collector layer 10, the active material particles 25 contained in the active material layer 24 will have difficulty entering the recess of the current collector layer 10, and therefore it will be difficult to improve the adhesion between the current collector layer 10 and the active material layer 24 laminated on top of it.
[0018] As shown in Figure 2, in this disclosure, the "entrance to the recess" can mean a position at a depth of 1 / 10 of the depth of the recess 10a from the surface of the current collector layer. Also, the "central part of the recess" can mean a position at a depth of 5 / 10 of the depth of the recess 10a from the surface of the current collector layer.
[0019] Furthermore, as shown in Figure 2, in this disclosure, "width of the recess entrance" can mean the width of the recess 10a at the "recess entrance" in a cross-section of the current collector layer 10 in the thickness direction passing through the center of the recess 10a. Similarly, as shown in Figure 2, in this disclosure, "width of the central part of the recess" can mean the width of the recess 10a at the "central part of the recess" in a cross-section of the current collector layer 10 in the thickness direction passing through the center of the recess 10a.
[0020] Furthermore, as shown in Figure 2, in this disclosure, "the inclination angle of the recess entrance with respect to the surface of the current collector layer" can mean the angle α between the surface of the current collector layer and the tangent to the surface of the recess 10a at "the recess entrance" in a cross-section of the current collector layer 10 in the thickness direction passing through the center of the recess 10a. Similarly, as shown in Figure 2, in this disclosure, "the inclination angle of the central part of the recess with respect to the surface of the current collector layer" can mean the angle β between the surface of the current collector layer and the tangent to the surface of the recess 10a at "the central part of the recess" in a cross-section of the current collector layer 10 in the thickness direction passing through the center of the recess 10a.
[0021] Furthermore, in relation to this disclosure, "D50 particle diameter of active material particles" can mean the particle diameter (median diameter) at 50% of the cumulative value in the volume-based particle size distribution obtained by laser diffraction-scattering for the active material particles.
[0022] The width of the entrance to the recess only needs to be wider than the width of the central part of the recess. For example, the width of the entrance to the recess may be 1.1 times or more, 1.3 times or more, 1.5 times or more, 1.8 times or more, or 2.0 times or more than the width of the central part of the recess, and may also be 5.0 times or less, 4.0 times or less, 3.0 times or less, 2.5 times or less, or 2.0 times or less.
[0023] The inclination angle of the entrance portion of the recess relative to the surface of the current collector layer only needs to be smaller than the inclination angle of the central portion of the recess relative to the surface of the current collector layer. For example, the inclination angle of the entrance portion may be 0.8 times or less, 0.7 times or less, 0.6 times or less, 0.5 times or less, 0.4 times or less, 0.3 times or less, 0.2 times or less, or 0.1 times or less of the inclination angle of the central portion, or it may be 0.1 times or more, 0.2 times or more, or 0.3 times or more.
[0024] Specifically, the inclination angle of the entrance section may be 50° or less, 40° or less, 30° or less, 20° or less, or 10° or less, and may also be 3° or more, 5° or more, or 10° or more. The inclination angle of the central section may be 120° or less, 90° or less, 80° or less, 70° or less, 60° or less, or 50° or less, and may also be 30° or more, 40° or more, or 50° or more.
[0025] The width of the entrance to the recess only needs to be greater than the D50 particle diameter of the active material particles contained in the active material layer. For example, the width of the entrance to the recess may be 2.0 times or more, 2.5 times or more, 3.0 times or more, 3.5 times or more, 4.0 times or more, 4.5 times or more, or 5.0 times or more of the D50 particle diameter of the active material particles, and may also be 10.0 times or less, 9.0 times or less, 8.0 times or less, 7.0 times or less, or 6.0 times or less.
[0026] The depth of the recess only needs to be greater than the D50 particle diameter of the active material particles contained in the active material layer. For example, the depth of the recess may be 2.0 times or more, 2.5 times or more, 3.0 times or more, 3.5 times or more, 4.0 times or more, 4.5 times or more, or 5.0 times or more than the D50 particle diameter of the active material particles, and may also be 10.0 times or less, 9.0 times or less, 8.0 times or less, 7.0 times or less, or 6.0 times or less.
[0027] The depth of the recess may be, for example, 10.0 times or less, 9.0 times or less, 8.0 times or less, 7.0 times or less, or 6.0 times or less the width of the entrance to the recess, or it may be 0.1 times or more, 0.5 times or more, 1.0 times or more, 2.0 times or more, 3.0 times or more, 4.0 times or more, or 5.0 times or more.
[0028] <Current collector layer> In the electrode laminate of this disclosure, the material of the current collector layer is not particularly limited, but a conductor commonly used for battery electrodes can be appropriately adopted. Examples of materials for the conductive layer include, but are not limited to, Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, stainless steel, etc. The current collector layer may also be a metal foil or a substrate on which the above metals are plated or vapor-deposited. The current collector layer may also be a resin current collector that provides conductivity by containing conductive particles in the resin. The current collector layer may also have a carbon coating on its surface.
[0029] The shape of the current collector layer is not particularly limited, but examples include foil-like, plate-like, etc. Among these, the foil-like shape is preferred.
[0030] The thickness of the current collector layer is not particularly limited, but may be 0.1 μm or more, or 1 μm or more, or 1 mm or less, or 100 μm or less.
[0031] <Active material layer> In the electrode stack of this disclosure, the active material layer contains active material particles. The active material layer may also optionally contain a binder, a conductive additive, and other components. Furthermore, if the electrode stack of this disclosure is an electrode stack for a solid-state battery, i.e., an electrode stack for a battery using a solid electrolyte, the active material layer may contain a solid electrolyte.
[0032] With respect to this disclosure, the "active material particles" may be either "negative electrode active material particles" or "positive electrode active material particles."
[0033] (Negative electrode active material particles) The negative electrode active material particles are not particularly limited as long as they are materials having a lower potential compared to the positive electrode active material particles. When the electrode stack of this disclosure is an electrode stack for a lithium-ion secondary battery, the negative electrode active material particles may include, for example, carbonaceous materials such as graphite (artificial graphite, natural graphite), resin carbon, carbon fiber, activated carbon, hard carbon, and soft carbon; metallic materials mainly consisting of tin, tin alloys, silicon, silicon alloys, gallium, gallium alloys, indium, indium alloys, aluminum, and aluminum alloys; conductive polymers such as polyacene, polyacetylene, and polypyrrole; metallic lithium; Li4Ti5O 12 Examples include lithium titanium composite oxides such as Li-Si alloys, Li-Sn alloys, Li-Al alloys, Li-Ga alloys, Li-Mg alloys, Li-In alloys, and other lithium alloy particles. These negative electrode active material particles may be used individually or in combination of two or more types.
[0034] The content of negative electrode active material particles in the active material layer is not particularly limited, but may be 50% by mass or more, 70% by mass or more, 90% by mass or more, or 95% by mass or more.
[0035] (Cathode active material particles) The positive electrode active material particles are not particularly limited as long as they are materials having a noble potential compared to the negative electrode active material. When the electrode stack of this disclosure is an electrode stack for a lithium-ion secondary battery, the positive electrode active material may be, for example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), solid solution oxide (Li2MnO3-LiMO2 (M=Co, Ni, etc.)), lithium nickel manganese oxide (LiNi1 / 2Mn1 / 2O2), lithium nickel cobalt manganese oxide (LiNi1 / 3Mn1 / 3Co1 / The following can be used: composite oxides such as 3O2, olivine-type lithium phosphate oxide (LiFePO4); conductive polymers such as polyaniline and polypyrrole; sulfide-based positive electrode active materials such as Li2S, CuS, Li-Cu-S compounds, TiS2, FeS, MoS2, Li-Mo-S compounds, Li-Ti-S compounds, and Li-VS compounds; materials using sulfur as an active material, such as sulfur-impregnated acetylene black, sulfur-impregnated porous carbon, and mixed powders of sulfur and carbon; etc. These positive electrode active materials may be used individually or in combination of two or more.
[0036] The content of positive electrode active material particles in the active material layer is not particularly limited, but may be 50% by mass or more, 70% by mass or more, 90% by mass or more, or 95% by mass or more.
[0037] (binder) The binder is not particularly limited and includes, for example, polyvinylidene fluoride (PVdF), polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamide-imide, polyvinyl alcohol, polyacrylonitrile, polyacrylic acid, polymethyl polyacrylate, polyethyl polyacrylate, polyhexyl polyacrylate, polymethacrylic acid, polymethyl polymethacrylate, polyethyl polymethacrylate, polyhexyl polymethacrylate, polyvinyl acetate, polyvinylpyrrolidone, polyether, polyethersulfone, polyhexafluoropropylene, styrene-butadiene rubber, carboxymethylcellulose, etc. These binders may be used individually or in combination of two or more.
[0038] The binder content in the active material layer is not particularly limited and can be set as appropriate depending on the desired binding properties, etc.
[0039] (Conductive additive) Examples of conductive additives are not particularly limited and include graphites such as natural graphite and artificial graphite; carbon blacks such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers such as carbon nanotubes and metal fibers; metal powders such as aluminum powder; conductive whiskers such as zinc oxide whiskers and conductive potassium titanate whiskers; conductive metal oxides such as titanium oxide; and organic conductive materials such as phenylene derivatives. These conductive additives may be used individually or in combination of two or more.
[0040] The content of the conductive additive in the active material layer is not particularly limited and can be set as appropriate depending on the desired conductivity, etc.
[0041] (solid electrolyte) The solid electrolyte is not particularly limited and may be, for example, a sulfide solid electrolyte, an oxide solid electrolyte, or a polymer electrolyte.
[0042] Examples of sulfide solid electrolytes include, but are not limited to, sulfide-based amorphous solid electrolytes, sulfide-based crystalline solid electrolytes, or argyrodite-type solid electrolytes. Sulfide solid electrolytes and oxide solid electrolytes may be glass or crystallized glass (glass ceramics).
[0043] Examples of polymer electrolytes include, but are not limited to, polyethylene oxide (PEO), polypropylene oxide (PPO), and copolymers thereof.
[0044] (Manufacturing method) The electrode stack of this disclosure can be manufactured by any method, and in particular by the method of this disclosure described below.
[0045] <<Battery>> The battery of this disclosure has the electrode stack of this disclosure.
[0046] Specifically, if the active material layer of the electrode stack of this disclosure is the negative electrode active material layer, the battery of this disclosure may have the positive electrode current collector layer, the positive electrode active material layer, the separator layer / solid electrolyte layer, the negative electrode active material layer of the electrode stack of this disclosure, and the current collector layer (negative electrode current collector layer) of the electrode stack of this disclosure in this order. Also, if the active material layer of the electrode stack of this disclosure is the positive electrode active material layer, the battery of this disclosure may have the current collector layer (positive electrode current collector layer) of the electrode stack of this disclosure, the positive electrode active material layer of the electrode stack of this disclosure, the separator layer / solid electrolyte layer, the negative electrode active material layer, and the negative electrode current collector layer in this order.
[0047] If the battery of this disclosure is a liquid-type battery, the positive electrode active material layer, the separator layer / solid electrolyte layer, and the negative electrode active material layer are impregnated with an electrolyte. Alternatively, the battery of this disclosure may be a solid-state battery, i.e., a battery using a solid electrolyte.
[0048] <<Manufacturing method for current collector layer>> As illustrated in Figure 4, the manufacturing method of the current collector layer of the present disclosure includes the following steps: A mask layer 30 having an opening 30a is laminated onto the surface of the metal foil 10p (Figure 4(a)), The metal foil 10p is etched through the opening 30a of the mask layer 30 to form a preliminary recess 10x on the surface of the metal foil 10p (Figure 4(b)). Removing the mask layer 30 from the metal foil 10p (Figure 4(c)), and The metal foil 10p from which the mask layer 30 has been removed is etched to obtain the current collector layer 10 (Figure 4(d)).
[0049] Details of the current collector layer obtained by this method can be found in the description of electrode stacks in this disclosure. Figure 4 is not intended to limit this disclosure in any way, but is merely illustrative of this disclosure.
[0050] When etching the metal foil 10p through the opening 30a of the mask layer 30 to form a preliminary recess 10x on the surface of the metal foil 10p, in particular when wet etching the metal foil 10p to form the preliminary recess 10x on the surface of the metal foil 10p, a phenomenon called undercutting can occur, as shown in Figure 4(b), causing the etching to progress to the underside of the mask layer 30. As a result, the width of the entrance to the recess formed by etching may become narrower than the width of the central part of the recess.
[0051] In contrast, in the method for manufacturing the current collector layer of this disclosure, after removing the mask layer 30 from the metal foil 10p, the metal foil 10p from which the mask layer 30 has been removed is etched again, particularly by an immersion etching method, thereby preferentially removing the entrance portion of the recess and widening the entrance portion, thereby obtaining the current collector layer used in the electrode laminate of this disclosure.
[0052] In the step of laminating a mask layer 30 having openings onto the surface of the metal foil 10p (Figure 4(a)), for example, a grid pattern of etching resist is formed on the metal foil. The etching resist can be formed using a general photolithography technique. The diameter of the resist openings in the grid pattern corresponds to the diameter of the openings in the recesses of the metal foil, and can therefore be made larger than the diameter of the active material particles in the mixture slurry described later.
[0053] In the step of etching the metal foil 10p through the opening 30a of the mask layer 30 to form a preliminary recess 10x on the surface of the metal foil 10p (Figure 4(b)), for example, the surface on which the etching resist is formed is etched using a spray etching method with an aqueous ferric chloride solution. At this time, the etching depth can be made larger than the active material particle size. By using the spray etching method, liquid diffusion can be made more efficient, and etching of the bottom of the recess can be promoted.
[0054] In the step of removing the mask layer 30 from the metal foil 10p (Figure 4(c)), for example, the etching resist is removed using an appropriate stripping solution.
[0055] In the step of etching the metal foil 10p from which the mask layer 30 has been removed to obtain the current collector layer 10 (Figure 4(d)), the obtained metal foil can be etched at the protrusions of the openings using an immersion etching method with an aqueous ferric chloride solution. By using the immersion etching method, openings where liquid diffusion is rapid can be preferentially etched.
[0056] <<Manufacturing method for electrode stacks>> The method disclosed herein for manufacturing the electrode stack of this disclosure is The current collector layer is manufactured by the method for manufacturing the current collector layer according to the present disclosure. A slurry of active material particles is applied to the current collector layer. Drying the active material layer slurry to form an active material layer. Includes.
[0057] The electrode stack of this disclosure can be manufactured by the method of this disclosure.
[0058] In the process of coating an active material layer slurry containing active material particles onto a current collector layer, for example, an electrode laminate can be manufactured by mixing and kneading active material particles, a conductive additive, and a binder in any mass ratio to obtain a composite paste, coating the resulting composite paste onto the current collector layer with a doctor blade, drying it, and pressing it. At this time, by making the diameter of the active material particles smaller than the width of the entrance to the recess in the current collector layer, the active material particles can be embedded in the recess.
[0059] In this disclosure, "active material layer slurry" means a slurry that, in addition to the constituent components of the active material layer, includes a dispersion medium, and can be applied and dried to form an active material layer. [Explanation of symbols]
[0060] 10 Current collector layer 10a Recess on the surface of the current collector layer 10 10p metallic foil 10x Pre-recessed surface of 10p metal foil 20 Active material layer of electrode laminate 100 of the present disclosure 22 Active material layer of conventional electrode stack 102 24 Active material layer of conventional electrode stack 104 25 Active material particles 30 mask layers 30a Opening of mask layer 30 100 electrode laminates disclosed 102 Conventional electrode stack 104 Conventional electrode stack α The inclination angle of the entrance portion of the recess 10a relative to the surface of the current collector layer 10. β The inclination angle of the central part of the recess 10a relative to the surface of the current collector layer 10
Claims
1. Current collector layer, and Active material layer disposed on the current collector layer An electrode laminate having, The current collector layer has a recess on the surface on which the active material layer is laminated, Some of the active material particles contained in the active material layer are embedded in the recesses. The width of the entrance portion of the recess is wider than the width of the central portion of the recess. The inclination angle of the entrance portion of the recess with respect to the surface of the current collector layer is smaller than the inclination angle of the central portion of the recess with respect to the surface of the current collector layer. The width of the entrance portion of the recess is greater than the D50 particle diameter of the active material particles contained in the active material layer. The depth of the recess is greater than the D50 particle diameter of the active material particles contained in the active material layer. Electrode stack.
2. The width of the entrance portion of the recess is 1.1 times or more the width of the central portion of the recess. The inclination angle of the entrance portion of the recess with respect to the surface of the current collector layer is 0.8 times or less the inclination angle of the central portion of the recess with respect to the surface of the current collector layer. The width of the entrance portion of the recess is 2.0 to 10.0 times the D50 particle diameter of the active material particles contained in the active material layer. The depth of the recess is 2.0 to 10.0 times the D50 particle diameter of the active material particles contained in the active material layer, and The depth of the recess is 10.0 times or less the width of the entrance to the recess. The electrode laminate according to claim 1.
3. A battery having the electrode stack according to claim 1 or 2.
4. A method for manufacturing a current collector layer, Laminating a mask layer having openings onto the surface of a metal foil, The metal foil is etched through the opening in the mask layer to form a preliminary recess on the surface of the metal foil. Removing the mask layer from the metal foil, and The metal foil from which the mask layer has been removed is etched to obtain the current collector layer. including and The current collector layer has a recess on the surface on which the active material layer is laminated, The width of the entrance portion of the recess is wider than the width of the central portion of the recess. The inclination angle of the entrance portion of the recess with respect to the surface of the current collector layer is smaller than the inclination angle of the central portion of the recess with respect to the surface of the current collector layer. A method for manufacturing a current collector layer.
5. To manufacture a current collector layer by the method described in claim 4, The active material layer slurry containing the active material particles is applied onto the current collector layer. The active material layer slurry is dried to form the active material layer. A method for manufacturing an electrode laminate according to claim 1, including the method described in claim 1.
Citation Information
Patent Citations
Carbon coated layer, paint, current collector, battery, forming method of carbon coated layer, and gravure plate
JP2019087489A
Conductive material-mixed electrode active material, electrode structure, secondary cell, AMD method for producing conductive material-mixed electrode active material
WO2003103076A1